Nitroaromatic explosives detection by a luminescent Cd(II) based metal organic framework. (17th February 2017) - Halder, Shibashis; Ghosh, Pritam; Rizzoli, Corrado; Banerjee, Priyabrata; Roy, Partha
Graphical abstract: A Cd(II) based three-dimensional coordination polymer, [Cd(3-bpd)(N(CN)2 )2 ] n (1 ), where 3-bpd is 1, 4-bis(3-pyridyl)-2, 3-diaza-1, 3-butadiene, has been synthesized and characterization by standard techniques including single crystal X-ray diffraction analysis.1 shows excellent detection ability towards trinitrophenol among several nitroaromatic compounds with high selectivity and sensitivity. Abstract: A Cd(II) based coordination polymer, [Cd(3-bpd)(N(CN)2 )2 ] n (1 ), where 3-bpd is 1, 4-bis(3-pyridyl)-2, 3-diaza-1, 3-butadiene, has been synthesized and characterized by standard methods including single crystal X-ray diffraction technique. Singly crystal X-ray diffraction analysis shows that it is a 3-dimensional metallo-organic framework.1 exhibits strong emission intensity in dispersed acetonitrile at 430 nm when it is excited at 340 nm. Among different explosive and pollutant nitroaromatic compounds (epNACs), trinitrophenol (TNP) is able to quench emission intensity of1 drastically making1 as the turn-off chemosensor for TNP. Other epNACs, e.g. 2, 4, 6-trinitrotoluene (TNT), 2, 6-dinitro toluene (2, 6-DNT), nitrobenzene (NB), 1, 3-dinitro benzene (1, 3-DNB), 3, 4-dinitrotoluene (3, 4-DNT) and 4-nitrobenzoic acid (4-NBA) cannot quench the emission intensity of1 significantly. The quenching constant value of1 for TNP has been determined to be 7.16 × 10 4 M −1 . Limit of detection of the complex towards TNP is 6 × 10 −5 M. Resonance energy transfer (RET) is involved in the transfer of energy from the electronically excited donor, 1 to the acceptor, TNP thereby quenching the emission intensity. Some theoretical calculations have been performed to support the electronic transitions and the proposed mechanism.